2000
DOI: 10.1038/sj.bjp.0703341
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence that 5‐HT‐induced relaxation of pig pulmonary artery is mediated by endothelial 5‐HT2B receptors

Abstract: 1 The endothelial 5-HT receptor mediating relaxation of pig pulmonary artery has been characterized using the selective 5-HT 2B receptor agonist BW 723C86 and a variety of structurally diverse 5-HT receptor antagonists. 2 If arterial rings with intact endothelium were precontracted with prostaglandin F 2a (3 mM), BW 723C86 caused concentration-dependent relaxation with a pEC 50 =8.21+0.03 and E max =89+4% relative to 5-HT. The relaxant responses to BW 723C86 were inhibited by the 5-HT 2B receptor antagonist SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 33 publications
0
51
0
2
Order By: Relevance
“…4). Such a result regarding 5-HT 2B receptors may not be very surprising since it has been previously shown that 5-HT 2B receptors induce a relaxation mediated by endothelial 5-HT 2B receptors in pig pulmonary arteries [21].…”
Section: Effect Of 5-ht On Camentioning
confidence: 87%
“…4). Such a result regarding 5-HT 2B receptors may not be very surprising since it has been previously shown that 5-HT 2B receptors induce a relaxation mediated by endothelial 5-HT 2B receptors in pig pulmonary arteries [21].…”
Section: Effect Of 5-ht On Camentioning
confidence: 87%
“…5-HTR 2B is expressed in human PAEC and stimulates calcium release (47). 5-HTR 2B elicits a reversible endothelium-dependent relaxation of pulmonary arteries in pigs, associated with an increase in cyclic GMP (11), through coupling to NO signaling pathway (30). Loss of function of 5-HTR 2B has been incriminated in fenfluramine-associated PAH (4).…”
Section: Expression Of Genes Related To Nf-b Pathway In Crpstimulatedmentioning
confidence: 99%
“…30,31) Atypical 5-HT receptors that mediate endothelium-dependent relaxation have been detected in numerous blood vessels. While some were initially classified as 5-HT 1 -like (a heterogeneous group that is currently subdivided into 5-HT 1B , 5-HT 1D , 5-HT 7 ) 32) (pig coronary arteries, 33) porcine vena cava 34) ), others may be tentatively classified as subtypes of the 5-HT 2 type (rabbit jugular vein, 35) rat jugular vein, 5,25) porcine pulmonary arteries 3,4,36) ). Taking this into account as well as the presence of mRNA for 5-HT 2B and 5-HT 1B in rat aorta, 2) we have focused on the pharmacological characterization of these types of receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this receptor, 5-HT 2B , 5-HT 1B , and 5-HT 7 mRNAs have been detected in this tissue 2) by polymerase chain reaction (PCR) techniques. The corresponding receptors mediate different responses in the isolated preparations where they have been functionally described: the 5-HT 2B receptor has been located in the endothelium of pig pulmonary artery 3,4) and rat jugular vein, 5) mediating relaxation. It has also been proposed that this receptor in smooth muscle mediates vasoconstriction in the mesenteric artery of mineralocorticoid hypertensive rats.…”
mentioning
confidence: 99%